Investigating disturbances of the core material system in the lung-gut axis of COPD based on the transcriptomics-metabolomics-microbiomics integration strategy - Tianyang Wang; Fang Wang; Ruinan Ren; Yikun He; Qi Yu; Guoan Zhao; Jinling Zhang; Qi Liu; Ying Lyu; Weiwei Jia; Wenbao Wang; Fanchen Meng; et al. (Arabian Journal of Chemistry)
Background: Although still the significance of the lung-gut axis for COPD is increasingly highlighted, it’s urgent to ulteriorly comprehend the sophisticated disturbance of the core material system along the lung-gut axis, which is of great importance for the accurate precaution and prognosis of COPD efficiently. Aim of the study: The purpose of this study was to analyze the information connections of the lung-gut axis, thus supporting the effective treatment of COPD. Materials and methods: An integrated multi-omics approach was applied to explore the lung-gut axis in COPD rats. Firstly, based on transcriptomics, the ssGSEA algorithm was used to evaluate changes in pulmonary inflammatory cells. Then, the disturbances of metabolic pathways in lung and feces were revealed by the Lilikoi algorithm using LC-MS and 1H NMR metabolomics. Next, the composition and function of microbial communities in lung and feces were analyzed by 16 s rRNA sequencing. Finally, the association analysis was employed to explore the possible crosstalk between the lung and gut. Furthermore, the core material system in the lung-gut axis was described based on network topology analysis. Result: Firstly, 1652 differential expression genes (involving in immune response-regulating signaling pathway, etc.) and 15 types of inflammatory cells (including neutrophil, etc.) were identified related to COPD. 135 pulmonary differential metabolites (involving in arachidonic acid metabolism, etc.) and 105 fecal differential metabolites (involving in alanine metabolism, etc.) were revealed by metabolomics. The f_Pasteurellaceae, etc. and g_Ruminococcus_2, etc. were identified associated with COPD in lung and gut. Finally, disturbances of the core material system, composed of macrophage, neutrophil, activated dendritic cell, myeloid derived suppressor cell, arachidonic acid metabolism, alpha linolenic acid & linoleic acid metabolism, g_Psychrobacter in lung and bile secretion, p_Proteobacteria in gut, were obtained to analyze the possible information flow of the lung-gut axis. Conclusion: The core material system for the lung-gut axis have been revealed, which might contribute to the illustration of the pathogenesis of COPD. In the future, more researches are required on the impact of the core material system in the lung-gut axis on the onset and recovery process of COPD, suggesting more precise identifying effective treatments for the disease.